Cyberbullying in private and state elementary schools in two Metropolitan Lima districts - Amemiya, Isabel (2013)
Objectives: To determine cyberbullying characteristics in Jesus Maria and Pueblo Libre districts 5th and 6th grade students from state and private schools. Design: escriptive, cross sectional. Setting: Students from state and private schools. Participants: 5th and 6th grade students. Interventions: Rosario Ortega’s anonymous survey was applied in 826 5th and 6th grade students. Main outcome measures: Descriptive analysis and statistical association tests. Results: Cyberbullying was reported in 24.7% students; it was higher in 6th grade, and in private schools. Aggressors by phone and internet were 1.9%, phone victims 6.3% and internet victims 12%.Internet victims’ condition was associated with having computer at their bedrooms (p=0.019) and using Internet outdoors (p=0.000); it was higher in private schools (p=0.002) and increased to 23.1% (p=0.032) when using Internet outdoors. Males assaulted more than females (p=0.000). Conclusions: Cyberbullying was more common in 6th grade students from private schools. Internet victims were more than phone victims; internet bullying was associated with having computer in their room or using it outdoors. Aggression predominated in males.